Training of Operators of Word Processing Machined (Microsoft Word) for Kepohkidul Village Equipment, Kedungadem Subdistrict, Bojonegoro Regency - Abidin, Zainul; Efendi, Agus; Santosa, Eka Budi (Social, Humanities, and Educational Studies (SHES): Conference Series, 2023)
Information and Communication Technology (ICT) is growing rapidly now-adays. This enables the adoption of technology in every sector of human life including work routines. However, training on the use of the Word Pro-cessing Machine (Microsoft Word) computer program received less attention so that knowledge and skills in operating the Word Processing Machine (Mi-crosoft Word) became lacking. Therefore, this study aims to provide basic competence in using a computer program, namely a Word Processing ma-chine (Microsof Word) to Kepohk idul village officials for publishing infor-mation and village administration services. Such training reduces the digital gap, enriches the potential of village officials, and promotes more use of public services. Fairness in developing communities. Kepohkidul Village is a village located in Kedungadem Subdistrict, Bojonegoro Regency, East Java Province. Currently Kepohkidul Village in terms of publishing information and administrative services has not been maximized. Efforts to improve the capabilities of Kepohk idul Village Officials, village heads and village secre-taries aim to make training this is to maximize the role of Kepohkidul village officials in providing services to the community, the method of implement-ing this service is in service training and on service training. The result of this activity is that Kepohkidul village officials have been able to operate word processing machines (microsoft word), so they are able to support publica-tions village information and daily administrative services to the community.